A concepção dos discentes do curso de Licenciatura em Ciências - Biologia e Química do Instituto de Educação, Agricultura e Ambiente (IEAA-UFAM) sobre o uso das tecnologias de informação e comunicação (TICs) no ensino de química - Silva, Luiz Eduardo Lima da (Brasil, 2019)
The technological advances caused changes in the educational context, so it was discussed the role of Information and Communication Technologies (ICTs) in Education, its implications in the school environment as a didactic tool and how initial teacher training should be modified to appropriate of this "novelty" and to use it in a way that promotes the quality of Teaching. Faced with the authors discussing the use of ICT in teaching chemistry and its implications for initial teacher training, this project aimed to analyze the conceptions of students of the course of Sciences: Biology and Chemistry on the use of ICT as a didactic resource for Teaching Chemistry. It was a descriptive-qualitative research, for which we conducted interviews with semi-structured questionnaires containing open and closed questions. The aim of this research was the students of the course who previously studied the subjects of Curricular Practice in Chemistry and were, at the time of the research, able to carry out or had carried out the discipline of Supervised Internship in Chemistry. This research was carried out at the Institute of Education, Agriculture and Environment of the Federal University of Amazonas, located at the headquarters of the municipality of Humaitá -AM. Based on the data obtained, it can be observed that most of the interviewees have constant contact with ICTs in their daily lives, making use of them and being aware of how to use it, albeit superficially, in their favor to carry out research and to plan their pedagogical activities. Among the technologies most used are the mobile phone, the notebook and the internet, fundamental pieces throughout the Supervised Stage. Some difficulties were mentioned, but it was not possible to explore in depth what they were or what caused them.